Comparison of myosin heavy chain mRNAs, protein isoforms and fiber type proportions in the rat slow and fast muscles - Zurmanová, J; Soukup, T (Physiological research, 2013)
We studied the expression of myosin heavy chain isoforms at mRNA and protein levels as well as fiber type composition in the fast extensor digitorum longus (EDL) and slow soleus (SOL) twitch muscles of adult inbred Lewis strain rats. Comparison of the results from Real Time RT-PCR, SDS-PAGE and fiber type analysis showed corresponding proportions of MyHC transcripts (MyHC-1, -2a, -2x/d, -2b), protein isoforms (MyHC-1, -2a, -2x/d, -2b) and fiber types (type 1, 2A, 2X/D, 2B) in both muscles. Furthermore, we found that slow MyHC-1 mRNA expression in the SOL was up to three orders higher than that of fast MyHC transcripts. This finding can explain the predominance of MyHC-1 isoform and fiber type 1 and the absence of pure 2X/D and 2B fibers in the SOL muscle. Based on our data presenting quantitative evidence of corresponding proportions between mRNA level, protein content and fiber type composition, we suggest that the Real Time RT-PCR technique can be used as a routine method for analysis of muscle composition changes and could be advantageous for the analysis of scant biological samples such as muscle biopsies in humans.
Keywords: Electrophoresis, Polyacrylamide Gel; messenger RNA; elektroforéza v polyakrylamidovém gelu; regulace genové exprese; Rats, Inbred Lew; Female; krysa rodu Rattus; svalová vlákna typu II; zvířata; Immunohistochemistry; těžké řetězce myosinu; Myosin Heavy Chains; imunohistochemie; protein - isoformy; Muscle Fibers, Fast-Twitch; Protein Isoforms; RNA, Messenger; ženské pohlaví; Gene Expression Regulation; Muscle Fibers, Slow-Twitch; svalová vlákna typu I; potkani inbrední LEW; Real-Time Polymerase Chain Reaction; Rats; Animals; kvantitativní polymerázová řetězová reakce